Development of Standardized Cyanthillium cinereum (L.) H.Rob. Extract and Determination of its Biological Activities - Kaji, Mafusol; Puttarak, Panupong (Natural Products Journal, The, 2022)
Aim: The development of a suitable standardized Cyanthillium cinereum (L.) H.Rob. extract is an active ingredient in healthcare products. Background: C. cinereum is the herbal tea specified in the Thai National List of Essential (herbal) Medicines (NLEM) as the most efficacious tea for smoking cessation. However, herbal tea is inconvenient, and no standardized C. cinereum extraction method was known. Objectives: The study aims to develop a standardized C. cinereum extract preparation method and determine its biological activities. Methods: Various extraction and fractionation methods were performed in order to optimize a suitable standardized extract. The extraction yield, biological activities, and biomarkers (apigenin and luteolin) of the HPLC method were used to select the most suitable extraction method. Results: The results showed that the Microwave-Assisted Extraction (MAE) method with 75% EtOH was the most suitable method. The MAE method obtained apigenin and luteolin at 0.320±0.029 and 0.487±0.012 mg/g, respectively. MAE showed good anti-inflammatory and antioxidant (DPPH and FRAP assay) activities. Subsequently, the MAE extract was fractionated by the Diaion® HP-20 column in order to obtain the most suitable standardized extract. The 50% plus 75% EtOH fractions showed high apigenin (91.20±1.23 mg/g) and luteolin (167.00±0.49 mg/g) contents and exerted potent bioactivities. The standardized C. cinereum extract presented high effectiveness of NO inhibitory activity with an IC50 of 7.88±3.56 μg/mL, and also exerted DPPH scavenging efficacy with an IC50 value of 8.88±0.17 μg/mL and quercetin equivalent at 137.50±2.20 mg/g by FRAP assay. Conclusion: This study succeeded in developing a high-yield extraction method of standardized C. cinereum extract, with potent antioxidant and anti-inflammatory activities, suitable for various purposes.
Keywords: antioxidant